IMPLEMENTATION OF THE KANO METHOD AND ANALYSIS OF ITS IMPORTANCE AND PERFORMANCE IN THE DEVELOPMENT OF THE PUSKESMAS SERVICE SYSTEM - Anisah, Siti (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2024)
Puskesmas is a community health service. Improving public health services can be achieved through providing excellent and quality health services. In terms of the performance of the puskesmas administrative services, there is no information system for processing patient data, which has an impact on the quality of services in the puskesmas. The aim of this research is to create a web-based knowledge management system that assesses the quality of health services provided by health centers. This will measure the gap between the actual performance of the Puskesmas, patient expectations, and the level of satisfaction experienced by patients. The system will also propose alternative solutions to increase patient satisfaction. in improving the quality of services provided by Community Health Centers. The methods used in the research are Importance and Performance Analysis (IPA) and the Kano method. The reason for choosing the IPA method is because IPA can be used to measure respondents' mastery of research attributes and can also measure the importance of an attribute based on respondents' perceptions. This research uses the Kano technique to categorize the features of a product or service based on their ability to fulfill customer desires effectively. The result of this research is a Knowledge Management System designed for Community Health Center services, which has the potential to reduce knowledge gaps.